The “Recognition Turn” in Critical Theory as a Communication Theory for Peace - McLuskie, Ed (Javnost-The Public, 2007)
The theory of communicative action is less associated with the idea of peace than with the cultivation of infrastructures for democratic interaction on the model of reasoned reciprocity. The theory is also marked by reflexive and historical attention to its distance from practice, thereby associating the theory with the critical diagnosis of the age. Such associations invite an action perspective on peace as a critical project oriented toward reasoned discourse. The paper explores the contributions of the theory of communicative action by taking one of its fundamental assumptions as a starting point: the recurring theme of mutual recognition. By exploring extensions of this theme into articulations of democratic and rational discourse, the paper off ers mutual recognition as a basis for the theory as a communicative idea of peace for the continuation and development of peace studies.